TAREKAT KEBANGSAAN: Kajian Antropologi Sufi Terhadap Pemikiran Nasionalisme Habib Luthfie - Imam Kanafi (Jurnal Penelitian, 2013)
The focus of this study are: what exactly is behind the surge of nationalism of Habib Luthfi bin Yahya Pekalongan as a head thariqah mu'tabarah Jam `iyya ahl al - nahdhiyyah; how exactly his view of state and nationality in the tarekat perspective; and what efforts made by him to serve as a vehicle for planting nationalism among the tarekat adherent. Documentation, participant observation, and in- dept interview were used to explore the needed data to answer those questions. To analysis data, anthropological approach was used. The results showed that Habib Lutfi bin Yahya who is of Arab descent among sayyid born in Pekalongan and lived in conditions and situations of a family that had a high khidmah to the social problems of Indonesian nationality. Extensive social relations with various communities had formed his thought to be pluralist and multukultural. To him, love for nation is a manifestation of the love of God and the Prophet. NKRI is set in stone, because Indonesia is the result of religious leaders of the struggle to ensure the realization of a just social system and prosperity to the consummation ta'abudiyah to God. The Indonesian people should not forget the history of his people, through the introduction of, respect for and taking the value of their role models. The strongnese of NKRI was a means of the realization of general welfare, so that the existence NKRI was necessary or obligatory. The implication of this was that to guard, to nurture and to respect the legitimate leader were also religious imperative. In the teachings of any congregation, positive thingking, and supporting the realization of brotherhood and security that it is the responsibility of government should be promoted.